A Potential Role of Salmonella Infection in the Onset of Inflammatory Bowel Diseases - Schultz, Bárbara M.; Paduro, Carolina A.; Salazar, Geraldyne A.; Salazar-Echegarai, Francisco J.; Sebastián, Valentina P.; Riedel, Claudia A.; Kalergis, Alexis M.; Alvarez-Lobos, Manuel; Bueno, Susan M. (Frontiers in Immunology, 2017)
Inflammatory Bowel Disease (IBD) includes a set of pathologies that result from a deregulated immune response that may affect any portion of the gastrointestinal tract. The most prevalent and defined forms of IBD are Crohn’s disease and ulcerative colitis. Although the etiology of IBD is not well defined, it has been suggested that environmental and genetic factors contribute to disease development, and that the interaction between these two factors can trigger the pathology. Diet, medication use, vitamin D status, smoking and bacterial infections have been proposed to influence or contribute to the onset or development of the disease in susceptible individuals. The infection with pathogenic bacteria is a key factor that can influence the development and severity of this disease. Here, we present a comprehensive review of studies performed in human and mice susceptible to IBD, which support the notion that infection with bacterial pathogens, such as Salmonella, could promote the onset of IBD due to permanent changes in the intestinal microbiota, disruption of the epithelial barrier and alterations of the intestinal immune response after infection.